What drives crowdfunding participation? The influence of personal and social traits. Issue 2 (15th May 2018) - Rodriguez-Ricardo, Yusimi; Sicilia, María; López, Manuela
Abstract : Purpose: Crowdfunding has become a popular and achievable means of funding projects worldwide. The purpose of this study is to determine which personal and social traits can increase individuals' intention to participate in crowdfunding. Design/methodology/approach: This study examines innovativeness, attitudes toward helping others and interpersonal connectivity as determinants of consumers' intention to participate in crowdfunding. Social identification with the crowdfunding community is proposed as a mediator in the model. Findings: The results show that both social identification with the crowdfunding community and innovativeness have a positive effect on intention to participate. In addition, attitudes toward helping others and interpersonal connectivity indirectly affect intention to participate in crowdfunding through social identification with the crowdfunding community. Research limitations/implications: This study analyzes a general audience of potential crowdfunders; therefore, the results identify just the indications for potential intentions to participate in crowdfunding activities. Practical implications: Companies or fund-seekers currently using or expecting to use crowdfunding have to develop strategies focused on promoting social identification with the crowdfunding community. More effort should be devoted for developing consumers' social relationships and ties within the crowdfunding community. Originality/value: This study contributes to the literature by clarifying the characteristics that potential crowdfunders should have to be more prone to participate in these types of projects. Abstract : Propósito de la investigación: El crowdfunding se ha convertido en un medio popular y factible de financiar proyectos en todo el mundo. El objetivo principal de este estudio es determinar qué características personales y sociales pueden aumentar la intención de los individuos de participar en el crowdfunding. Metodología y diseño: Esta investigación examina la capacidad de innovación, las actitudes hacia ayudar a los demás y la conectividad interpersonal como determinantes de la intención de los consumidores de participar en el crowdfunding. La identificación social con la comunidad de crowdfunding se propone como un mediador en el modelo. Recomendaciones: Los resultados muestran que tanto la identificación social con la comunidad de crowdfunding y la capacidad de innovación tienen un efecto positivo en la intención de participar en proyectos de crowdfunding. Además, las actitudes hacia ayudar a los demás y la conectividad interpersonal afectan indirectamente la intención de participar en el crowdfunding a través de la identificación social con la comunidad de crowdfunding. Limitaciones de investigación: Esta investigación analiza una audiencia general de posibles "crowdfunders", por lo tanto, los resultados identificaron solo indicaciones de intenciones potenciales para participar en actividades de crowdfunding. Implicaciones prácticas: Las empresas o emprendedores que actualmente usan o esperan usar el crowdfunding como método de financiación, deben desarrollar estrategias enfocadas en promover la identificación social con la comunidad de crowdfunding; así como fomentar el desarrollo de las relaciones y las relaciones sociales de los consumidores dentro de la comunidad de crowdfunding. Originalidad: Esta investigación contribuye a la literatura explicando las características sociales y personales de los individuos que con más propensión participarían en este tipo de proyectos.